2017
DOI: 10.1080/15389588.2017.1315109
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in emotion regulation and risky driving among Lithuanian drivers

Abstract: Emotion regulation difficulties were associated with the self-reported risky driving behaviors of Lithuanian drivers. This provides useful hints for improving driver training programs in order to prevent traffic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…The interventions designed to promote traffic safety in drivers of different ages, thus, should work on including emotion regulation strategies, specifically in traffic situations. In fact, recent empirical evidences (e.g., Šeibokaitë et al, 2017) showed difficulties in emotion regulation are significantly related with driving errors, lapses, aggressive violations, and ordinary violations in drivers of different ages. In this regard, experimental studies have demonstrated the effectiveness of cognitive, relaxation, and behavioral interventions – and their combinations – in reducing driving anger and aggression in angry drivers (for a review, see Deffenbacher, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The interventions designed to promote traffic safety in drivers of different ages, thus, should work on including emotion regulation strategies, specifically in traffic situations. In fact, recent empirical evidences (e.g., Šeibokaitë et al, 2017) showed difficulties in emotion regulation are significantly related with driving errors, lapses, aggressive violations, and ordinary violations in drivers of different ages. In this regard, experimental studies have demonstrated the effectiveness of cognitive, relaxation, and behavioral interventions – and their combinations – in reducing driving anger and aggression in angry drivers (for a review, see Deffenbacher, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Trógolo, Melchior, and Medrano (2014) also have found that more difficulties in different emotion regulation abilities were related to various forms of risky driving or specifically to the increase of texting-while-driving in young drivers group (Feldman, Greeson, Renna, & Robbins-Monteith, 2011). Šeibokaitė, Endriulaitienė, Sullman, Markšaitytė, and Žardeckaitė-Matulaitienė (2017) have found that difficulties with impulse control and difficulties engaging in goal-directed behaviour were related to more frequent self-reported risky driving of Lithuanian drivers. These relations between emotional regulation and behaviour outcomes of risky driving provide the reason to expect similar associations between emotional difficulties and attitudes.…”
Section: Introductionmentioning
confidence: 97%
“…Improper driving behavior not only relates to the driver's life and safety, but also increases a lot of hidden dangers, and even endangers the society. Driver's emotion, as one of the main psychological factors, is sometimes not controlled by cognition, and may spontaneously influence driving behaviors (Strongman, 2003;Šeibokaitė et al, 2017;Maldonado et al, 2020). Emotion is a short, easily affected, and rapidly changeable state of mind (Zimasa et al, 2016), which arises when something important to us is at stake and calls forth a coordinated set of behavioral, experiential, and physiological response tendencies that together influence how we respond to perceived challenges and opportunities (Gross, 2002).…”
Section: Introductionmentioning
confidence: 99%